The Effect of Use of Geogebra Media on Student Learning Result in Trigonometry Function Material in Class X Senior High School 8 Cirebon - Syafadol Zikri; Darwan Darwan; Sirojudin Wahid (International Journal of Education and Humanities, 2021)
One of the causes of the unattractiveness of learning mathematics for high school is the complexity factor of learning media that is in harmony with complex material. Therefore, learning media need a form of presentation that is simple but attractive. Efforts to increase student interest, which require media to support learning mathematics. One of them is by using Geogebra learning media. This study aims to determine the influence of the use of learning media based on the Geogebra application on student learning outcomes at Senior High School 8 Cirebon. The research method used is a quasi-experimental design, which is a research method that has a control group, but cannot function fully to control external variables that affect the implementation of the experiment. The results of the study obtained the value of F-count > Ftable or 26,358 > 4,13. And the correlation (r) = 0.661 then it is included in the medium category. The coefficient of determination (r2) = 0.437 or 43.7%, then the learning media has an effect on student learning outcomes on the subject of trigonometric functions. Based on the results of the Independent T-test analysis, the t-count value of 11,037 using a significance level of 5% obtained t-table of 1,994. The t-table value is obtained from the excel program by means of =tinv(0.05;69.) then enter. Because the value of t-count > t-table (11.037 > 1.994) then Ho is rejected. This means that Geogebra learning media can improve student learning outcomes